Muntok White Pepper Price Transmission in Bangka Belitung Island Province - Purwasih, Rati; Pranoto, Yudi Sapta; Atmaja, Eddy Jajang Jaya (Universitas Muhammadiyah Yogyakarta, 2020)
The average price of white pepper in the Bangka Belitung Islands Province from January 2007 to December 2016 was IDR 72,531 per kg on the producer market, IDR 80,622 per kg on the export market, and IDR 99,017 per kg on the world market. Based on the data, there is a large marketing margin between the producer market and the export market, IDR 8,091 per kg. While, the margin between the export market and the world market was IDR 18,395 per kg. The present research aims to analyze the transmission of white pepper prices in the Bangka Belitung Islands Province among the three markets. The Asymmetric Error Correction Model (AECM) was used as the model to analyze the transmission of white pepper prices in Bangka Belitung Island Province from producers to exporters, from producers to world market, and from exporters to world market. The transmission of white pepper prices from the three markets shows that in the short period it runs asymmetrically, whereas in the long period it runs symmetrically. Conversely, the transmission of white pepper prices from the world market to the exporters market runs symmetrically in the short term but it runs asymmetrically in the long term.